A case of left circumflex artery stenosis involving ST segment depression in multiple leads with ST elevation in lead augmented vector right - Karunadas, C. P.; Mathew, Cibu (International Surgery Journal, 2019)
Electrocardiography (ECG) patterns of ST-segment elevation in lead aVR with or without diffuse ST segment depression may predict either left main coronary artery or triple vessel stenosis. Here, we have presented the case of a 56-year-old female involving such an ECG pattern with ST-segment depression in more than eight leads and ST Segment elevation in lead aVR, however, showing stenosis of the mid-segment of the left circumflex artery (LCX). She was scheduled to undergo percutaneous coronary intervention with implantation of a drug-eluting stent with respect to mid LCX stenosis. The patient was asymptomatic post procedure and was discharged on beta blockers. To conclude, the ECG pattern of ST depression in multiple leads with ST-elevation in aVR lead can occur in LCX obstruction as well.